Juan Alfredo Casaubon, Palabras, ideas, cosas. El problema de los universales. Prólogo de Octavio Nicolás Derisi. Ediciones Candil, Buenos Aires, 1984, 240 pp - Sacchi, Mario Enrique (1991)
Fil: Sacchi, Mario Enrique. Armada Argentina. Escuela de Guerra Naval; Argentina